Integrated Assessment Level of Service Street and Road Environment to the Needs of Persons with Disabilities - Ivasenko, Viktoriia; Lytvynenko, Tetyana; Zhidkova, Tetyana; Tkachenko, Iryna (International Journal of Engineering and Technology, 2018)
The work defines the assessment criteria and formation of street and road environment to the needs of people with limited mobility for solution the fundamental principles for while addressing architectural and planning issues and theoretical foundations of long-term planning for urban mobility. Characteristics accessibility tools and the calculation method of certain parameters: density pedestrian flow; the width of the roadway; the time required to overcome the roadway people with disabilities; relative grip factor of wheels wheelchair road are specified.Suggested methods of comprehensive evaluation of street and road maintenance environment to the needs of people with limited mobility and the suggestions of streets and roads network and its elements improvement are elaborated. Â Â Â